The rectangle below has an area of x ^ 2 - 16 square meters and a width of x + 4meters . What expression represents the length of the rectangle?
The rectangle below has an area of x ^ 2 - 1

Answers

Answer 1
Answer:

Answer:

length=x-4

Step-by-step explanation:


Related Questions

One twelfth of the circle is 30 degrees. how many radians is one twelfth of the circle
What is the least common multiple of 2,6 and 15?
Convert 6 kilometers to yards
A radio station has a broadcast area in the shape of a circle with equation x^2+y^2=5 625
What is the value of 12.5 10^7?a. 12.5000000 b. 1,250,000 c. 125,000,000 d. 1.2500000

How many feet are in 96 inches?

Answers

since 1 foot = 12 inches just do 96 ÷ 12

96 ÷ 12 = 8

Therefore, 
There are 8 feet in 96 inches.  

Hope this helps and have a great day! :D 
8 because 12x8=96 and 12 inches in a foot

Which inverse operation would be used to verify the following equation?102 ÷ 3 = 34 

       A. 34 − 3 = 31   B. 3 + 34 = 37   C. 34 × 3 = 102   D. 102 ÷ 34 = 3

Answers

Another one is 34 times 3

Answer:

C. 34x3 would be you answer

Step-by-step explanation:


Is .32903 greater than 0.59

Answers

No, .32903 is not greater than 0.59
It does not matter how long is the number after the point. As 5 is bigger than 3, 0.32903 is smaller than 0.59

Ronnie wants to buya computer table that measures 10 feet by 17 feet.The cost of the table is $16 per square foot.How much will it cost Ronnie to buy the computer table for his study?

Answers

find how many square feet it is
assumng the table is a rectangle
area=legnth times width
area=10 times 17=170

16 per 1 square foot
16 imes 170=2720

answer is $2720

Simplify the expression
49(1)/(2)

Answers

To convert a mixed fraction into an improper fraction:

a(b)/(c) =((a\cdot c)+b)/(c)

49 (1)/(2) = ((49\cdot 2)+1)/(2) = (98 +1)/(2) = \boxed{\bf{(99)/(2)}}

Let f(x)=-4x+7 and g(x)=10x-6. Find f(g(x))

Answers

\bf \begin{cases}f(x)=-4x+7\ng(x)=10x-6\end{cases}\qquad \qquad f(~~g(x)~~)=-4[g(x)]+7\n\n\nf(~~g(x)~~)=-4[10x-6]+7\implies f(~~g(x)~~)=-40x+24+7\n\n\nf(~~g(x)~~)=-40x+31